Bipartite gating in the outer membrane protein FecA. (August 2002) - van der Helm, D.; Chakraborty, R.; Ferguson, A. D.; Smith, B. S.; Esser, L.; Deisenhofer, J.
Abstract : The recent structure determination of FecA, with and without ligand, shows the existence of two gates. These are the extracellular loops closing over the binding site and the plug located inside the barrel. It indicates a process which is described as bipartite gating and allows for a rational distinction between the binding event and the transport process.